1986
DOI: 10.1161/01.cir.73.4.662
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-induced coronary vasoconstriction in patients with atherosclerotic coronary artery disease: evidence for adrenergically mediated alterations in coronary artery tone.

Abstract: In patients with atherosclerotic coronary artery disease, cigarette smoking increases myocardial oxygen demand but may cause an inappropriate decrease in coronary blood flow and myocardial oxgyen supply. This study was performed to explore the mechanism of smoking-induced coronary vasoconstriction and, specifically, to determine if smoking causes an ct-adrenergically mediated increase in coronary artery tone. In 36 chronic smokers with coronary artery disease (27 men and nine women, 50 9 [mean + SD] years old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
1
10

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(85 citation statements)
references
References 21 publications
1
73
1
10
Order By: Relevance
“…23,24 Finally, smoking increases coronary resistance in patients with coronary artery disease, and this effect is counteracted by intravenous phentolamine. 41 Most of the above studies that observed constrictor responses either did not report on signs and symptoms of ischemia or reported angina in only a minority of patients with coronary artery disease. 19,20,24 Also, in most of these studies in which the cold pressor test or mental stress was used to induce sympathetic activation, there was no evidence of the ␣-adrenergic nature of the observed vasoconstriction, but intracoronary phentolamine induced a greater decrease in coronary resistance than placebo during mental stress.…”
Section: Enhanced ␣-Adrenergic Vasoconstriction In Patients With Estamentioning
confidence: 99%
“…23,24 Finally, smoking increases coronary resistance in patients with coronary artery disease, and this effect is counteracted by intravenous phentolamine. 41 Most of the above studies that observed constrictor responses either did not report on signs and symptoms of ischemia or reported angina in only a minority of patients with coronary artery disease. 19,20,24 Also, in most of these studies in which the cold pressor test or mental stress was used to induce sympathetic activation, there was no evidence of the ␣-adrenergic nature of the observed vasoconstriction, but intracoronary phentolamine induced a greater decrease in coronary resistance than placebo during mental stress.…”
Section: Enhanced ␣-Adrenergic Vasoconstriction In Patients With Estamentioning
confidence: 99%
“…Moreover, there is an increased rate of mortality in CABG patients who continue to smoke after surgery (Ashraf et al, 2004). Although nicotine-induced catecholamine release likely contributes to coronary vasospasm in smokers (Winniford et al, 1986), passive smoking also induces endothelial dysfunction, and thus aldehydes in cigarette smoke could contribute to vasospasm (Hausberg et al, 1997;Celermajer et al, 1996). Our model suggests that both exogenous and endogenous sources of acrolein could contribute to the risk of vasospasm.…”
Section: Clinical Significance Of Acrolein Exposure and Vasospasmmentioning
confidence: 77%
“…Importantly, acrolein is considered a co-pollutant of particulate matter, and particulate matter exposure is associated with increased cardiovascular morbidity and mortality of which some may be vasospasm-related (Peters, 2005). For example, cigarette smokers are at increased risk of coronary artery vasospasm (Quillen et al, 1993;Winniford et al, 1986) and a T −786 →C eNOS mutation increases risk of coronary artery vasospasm among Japanese men, especially smokers (Nakayama et al, 2003). Moreover, there is an increased rate of mortality in CABG patients who continue to smoke after surgery (Ashraf et al, 2004).…”
Section: Clinical Significance Of Acrolein Exposure and Vasospasmmentioning
confidence: 99%
“…Cigarette smoking increases vasoconstriction of the coronary arteries through an alpha-adrenergic mechanism similar to that of cocaine. 89 Recent studies have demonstrated that concomitant cigarette smoking substantially exacerbates the deleterious effects of cocaine on myocardial oxygen supply and demand. 6 Multi-drug interactions may additionally complicate anesthetic management of poly-substance-abusing pregnant patients.…”
mentioning
confidence: 99%